The German automobile industry and Central Europe’s integration into the international division of labour: foreign production, intraindustry trade, and labour market repercussions - Nunnenkamp, Peter (Papeles del Este, 2004)
Industrial relations in the German automobile industry are tense. The economic transformation of Central European countries has resulted in significantly increased competitive pressure, even though this industry is relatively technology and human-capital intensive and, thus, represents a traditional manufacturing stronghold of advanced countries such as Germany. Especially for low skilled production workers, the competition from Central Europe has intensified pressure on relative wages and impaired employment opportunities. For the industry as a whole, there is no reasonable alternative to innovation and specialization according to comparative cost advantages. Specialization will help secure employment and income opportunities for skilled workers, but it offers little relief to low skilled workers. Moreover, wage restraint will provide only part of the solution for low skilled workers in the German automobile industry. Unless they succeed to improve their Level of qualification, the employment and income prospects of this part of the labour force can be expected to deteriorate.